Designing "Meows .Co" Application as a Tool for Cat Lovers - Albanna Rahmadani S; Ikra Esa A'raaf Mahardika; Lingga Juliansyah (International Journal of Research and Applied Technology (INJURATECH), 2023)
Cats are one of the most common pets kept by humans. During a pandemic, keeping cats has many benefits for mental and physical health. The purpose of this research is to design a mobile-based application that functions as a tool for cat lovers who are still confused about how to take care of their cats, solutions to deal with the types of diseases or infections that can attack cats, and want to adopt cats. To support the research, the research method we use is descriptive, as well as in the application development process uses an object-oriented approach with System Development Life Cycle Waterfall. As a result, designing the Meows application makes it easier for cat lovers to find information using a digital platform that can be accessed through their respective smartphones. The concept of this application is to provide information to cat lovers about how to take good and correct care of their cats and features to share information about cats with other cat lovers. In the end, this application serves as a medium of information for cat lovers to get information more easily and help cat lovers with one another